The Influence of Merchandising, Basic Principles, and Services on Customer Satisfaction at a Hypermart Store Retail Business Company in Bengkulu City - Yudi Irawan Abi; Dewi Aprianti (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to examine the role of merchandising, basic principles, and services with customer satisfaction at the Hypermart Store company in the city of Bengkulu. This study uses a quantitative methodology to solve the problem. The sampling technique in this study used purposive sampling technique and data collection was carried out by distributing questionnaires to respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The number of samples is 200 customers at Hypermart Store company in Bengkulu city. The data analysis technique used in this study is the structural equation model (SEM) using Amos 21. Hypothesis testing using the Structural Model test. The results of this study indicate that merchandising has a significant positive effect on customer satisfaction, basic principles have a significant effect on customer satisfaction and services have a significant effect on customer satisfaction.